7(x-1)=6x+1

Simple and best practice solution for 7(x-1)=6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-1)=6x+1 equation:


Simplifying
7(x + -1) = 6x + 1

Reorder the terms:
7(-1 + x) = 6x + 1
(-1 * 7 + x * 7) = 6x + 1
(-7 + 7x) = 6x + 1

Reorder the terms:
-7 + 7x = 1 + 6x

Solving
-7 + 7x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-7 + 7x + -6x = 1 + 6x + -6x

Combine like terms: 7x + -6x = 1x
-7 + 1x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
-7 + 1x = 1 + 0
-7 + 1x = 1

Add '7' to each side of the equation.
-7 + 7 + 1x = 1 + 7

Combine like terms: -7 + 7 = 0
0 + 1x = 1 + 7
1x = 1 + 7

Combine like terms: 1 + 7 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| X^2-13x+60=90 | | 88=2+2(8-5x) | | 8x+6=5x+5 | | g-4=-3 | | 22=x^2 | | (-x^5/2)^4 | | m-9=3 | | y=1.2+0.8(-2) | | ln(x)+ln(5x)=9 | | -89=x+75 | | 9y-5y(6-8)= | | 12+6(z+2)=5z+2 | | pt+51=76 | | 7y+y(2-8)= | | 6-4x^5=4-3x^2 | | (6+x)(x)=28 | | 6-4x*5=4-3x*2 | | h+9=-45 | | 6+x(x)=28 | | -16t^2-120t+500=700 | | -19n+16=-18n-5 | | 43x=86 | | -19n+16=-18-5 | | 24+10x-x^2=p-(x-5)2 | | 15+6y=15y-3 | | 7x-25=-10 | | (2r-3)(2r+3)= | | t=6 | | 6y-8=3y-7 | | -16t^2+120t+500=700 | | -16t^2+120t+500=200 | | 10=14x-4-13x |

Equations solver categories